Android-based application to assist doctor with Alzheimer's patient - Habash, Zaid A.; Wan Ishak, Wan Hussain; Omar, Mohd. Hasbullah (2013)
Alzheimer‘s disease is one of the leading diseases that contribute to dementia cases. The Alzheimer‘s patient suffers from memory loss and losing judgment due to its effect on the human brain.Alzheimer‘s patients need to be monitored and assisted in their daily life especially for medication.Proper medication may reduce the effect of Alzheimer‘s disease on the patient.The Android-based mobile application is one of current technologies that can be used to assist doctors to monitor Alzheimer‘s patient medication.The application alert patient when to consume the medicine based on the schedule provided by the doctor.The application has been evaluated by doctors, where the responses are very satisfactory.